Neighborhood Predictors of Intimate Partner Violence: A Theory-Informed Analysis Using Hierarchical Linear Modeling. - Voith, Laura A.; Brondino, Michael J. (American Journal of Community Psychology, 2017)
Due to high prevalence rates and deleterious effects on individuals, families, and communities, intimate partner violence (IPV) is a significant public health problem. Because IPV occurs in the context of communities and neighborhoods, research must examine the broader environment in addition to individual-level factors to successfully facilitate behavior change. Drawing from the Social Determinants of Health framework and Social Disorganization Theory, neighborhood predictors of IPV were tested using hierarchical linear modeling. Results indicated that concentrated disadvantage and female-to-male partner violence were robust predictors of women's IPV victimization. Implications for theory, practice, and policy, and future research are discussed.